Using anchors from free text in electronic health records to diagnose postoperative delirium. (December 2017) - Mikalsen, Karl Øyvind; Soguero-Ruiz, Cristina; Jensen, Kasper; Hindberg, Kristian; Gran, Mads; Revhaug, Arthur; Lindsetmo, Rolv-Ole; Skrøvseth, Stein Olav; Godtliebsen, Fred; Jenssen, Robert
Highlights: The anchor framework is introduced as a diagnosis tool for postoperative delirium. A procedure based on clustering and data visualization is used to specify anchors. We increase the AUC-PR from 0.51 to 0.96 compared to baselines. Abstract: Objectives: Postoperative delirium is a common complication after major surgery among the elderly. Despite its potentially serious consequences, the complication often goes undetected and undiagnosed. In order to provide diagnosis support one could potentially exploit the information hidden in free text documents from electronic health records using data-driven clinical decision support tools. However, these tools depend on labeled training data and can be both time consuming and expensive to create. Methods: The recent learning with anchors framework resolves this problem by transforming key observations (anchors) into labels. This is a promising framework, but it is heavily reliant on clinicians knowledge for specifying good anchor choices in order to perform well. In this paper we propose a novel method for specifying anchors from free text documents, following an exploratory data analysis approach based on clustering and data visualization techniques. We investigate the use of the new framework as a way to detect postoperative delirium. Results: By applying the proposed method to medical data gathered from a Norwegian university hospital, we increase the area under the precision-recall curve from 0.51 to 0.96 compared to baselines. Conclusions: The proposed approach can be used as a framework for clinical decision support for postoperative delirium.